Effect of pyrolysis temperature on the transformation of phosphorus forms in sludge biochar - Zhongpu Yu; Weichao Yu; Xianjun Sun; Rumin Xu; Mengdi Liang; Jun Wang; Yuan Liang; Feiyue Li (Water Science and Technology, 2024)
The Standards, Measurements, and Testing (SMT) phosphorus fractionation approach was used to measure the amounts of total phosphorus (TP), organic phosphorus (OP), inorganic phosphorus (IP), apatite inorganic phosphorus (AP), and non-apatite inorganic phosphorus (NAIP) in sludge biochar. Sludge biochar was characterized using methods such as X-ray diffraction, elemental analysis, and Fourier transform infrared spectroscopy. The findings showed that IP content increased significantly after pyrolysis, reaching up to 97% of TP content at the optimal temperature of 350 °C. Furthermore, when the pyrolysis temperature increased, the AP/IP ratio showed fluctuations between decreases and increases, maximum at 60%. The results of the correlation analysis indicate that IP has a positive correlation with yield, pH, and S elements (p < 0.05) and a negative correlation with N, C, and H elements (p < 0.01). OP, on the other hand, has a positive correlation with H elements (p < 0.05) and a negative correlation with yield (p < 0.01). Furthermore, TP, NAIP, and AP all show negative correlations with N, C, and H elements (p < 0.01), with TP and NAIP also displaying negative correlations with pH and S elements (p < 0.05). HIGHLIGHT Phosphorus morphology changes at 300–700 °C by the Standards, Measurements, and Testing method. Different temperatures change the transformation of various phosphorus forms. The apatite inorganic phosphorus content in biochar increased with the increase of pyrolysis temperature and reached the maximum at 700 °C.;